2011
DOI: 10.1242/jeb.058354
|View full text |Cite
|
Sign up to set email alerts
|

Extracoelenteric zooplankton feeding is a key mechanism of nutrient acquisition for the scleractinian coral Galaxea fascicularis

Abstract: SUMMARYInternal and external feeding on zooplankton may provide scleractinian corals with important nutrients. However, the latter process has never been properly quantified. To quantify the dynamics of zooplankton capture, digestion and release for a scleractinian coral, we performed detailed video analyses of Galaxea fascicularis feeding on Artemia nauplii. A highly dynamic process of prey capture, digestion and release was observed. A single G. fascicularis polyp (N3) captured 558±67 and released 383±75 Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 31 publications
2
55
2
Order By: Relevance
“…, Wijgerde et al, 2011) by the duration of the feeding period (2 h) and then dividing this rate by the measured respiration rate converted to carbon equivalents with values normalized to tissue surface area (as per Hoogenboom et al, 2010). Energy allocation to skeleton growth was calculated from the measured total calcification across the experiment (g) multiplied by the energy cost of calcification (0.152 J mg −1 , Anthony et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…, Wijgerde et al, 2011) by the duration of the feeding period (2 h) and then dividing this rate by the measured respiration rate converted to carbon equivalents with values normalized to tissue surface area (as per Hoogenboom et al, 2010). Energy allocation to skeleton growth was calculated from the measured total calcification across the experiment (g) multiplied by the energy cost of calcification (0.152 J mg −1 , Anthony et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Another issue which should be addressed is how long the inhibitory effect of heterotrophy lasts, which is likely to be only several hours when taking feeding and digestion rates of G. fascicularis into account [31], [32]. A temporal effect would explain the discrepancy between the inhibitory short-term [11,12, this paper] and enhancing long-term [1] effects of heterotrophy on coral calcification.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the observed impairment of prey capture and retention at 1,000 nauplii L −1 was due to mucus grazing by flatworms, limiting the capacity of polyps to capture and retain more nauplii at higher prey concentrations. Indeed, Hii et al and Wijgerde et al found that, at high zooplankton concentrations in particular, G. fascicularis produces copious amounts of mucus, which is likely to facilitate the capture of higher amounts of prey (Hii et al, 2009; Wijgerde et al, 2011a). Finally, kleptoparasitism clearly contributed to a reduction of coral feeding by decreasing prey retention rates of the coral host (also see next section).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced resistance may result from feeding on coral mucus by flatworms, thereby removing (part of) the layer that protects the coral against sedimentation, dehydration, UV-radiation and pathogens (Barneah et al, 2007b; Brown and Bythell, 2005; Naumann et al, 2010). Moreover, prey capture may be impaired as mucus serves as an effective adhesive layer for capturing prey (Sorokin, 1990; Wijgerde et al, 2011a). …”
Section: Introductionmentioning
confidence: 99%